Intuitionistic Fuzzy Binary Soft Topological Spaces - Elluru, Vyshakha; Angadi, Bhadramma M.; Patil, P. G. (Communications in Mathematics and Applications, 2025)
In this article, intuitionistic fuzzy binary soft topological space over two initial universal sets and a parameter set is introduced. Further, intuitionistic fuzzy binary soft neighborhood, intuitionistic fuzzy binary soft interior, intuitionistic fuzzy binary soft closure in an intuitionistic fuzzy binary soft topological space is defined, and their properties are discussed.
Keywords: Intuitionistic fuzzy binary soft topological space; Intuitionistic fuzzy binary soft neighborhood; Intuitionistic fuzzy binary soft interior; Intuitionistic fuzzy binary soft closure